Highlighting enviromental education based on a problem-solving class about the usage and disposal of batteries (Research, Society and Development, 2021)
This study describes an application and analisys of a problem-solving class about the utilization and inadequate disposal of batteries, with the objective of promoting enviromental awareness of 9th grade students of a local public school. In this perspective, a pedagogical intervention obeyed the follwing problem-solving steps: (i) initially, a survey on the students' prior knowledge was conducted through a exam; (ii) afterwards, an expository-dialoged lecture was developed adressing elementary characteristics of the subject; (iii) then an out-of-class lesson was proposed involving substainable aspects of the use of batteries and, at last, (iv) a debate about the results. As a result, it was found that the students showed little understanding of the disposal of these wastes and conceptual basis about the subject. Nevertheless, following the dialogical-problematizing approach, it became apparent the diligence of the students in the theme based on daily noted observations. The extra-class surveys, contrastingly, demonstrated the perception of environmental consequences to the detriment of inadvertent disposal of these wastes, conveying to reverse logistics proposals, imposition of fines to offenders, and so on. Based on that, a parallel with the new presented insight, where it was noticed that the aprioristic neglect, on the part of the students, turned into a commitment in the adoption of sustainable attitudes. Thus, assesses that this strategic strand was successful subsidizing enough learning to develop environmental awareness about the correct use and disposal of this solid waste.